Acute stress enhances the expression of neuroprotection- and neurogenesis-associated genes in the hippocampus of a mouse restraint model - Sannino, Giuseppina (Oncotarget, 2016)
Stress arises from an external demand placed on an organism that triggers physiological, cognitive and behavioural responses in order to cope with that request. It is thus an adaptive response useful for the survival of an organism. The objective of this study was to identify and characterize global changes in gene expression in the hippocampus in response to acute stress stimuli, by employing a mouse model of short-term restraint stress. In our experimental design mice were subjected to a one time exposure of restraint stress and the regulation of gene expression in the hippocampus was examined 3, 12 and 24 hours thereafter. Microarray analysis revealed that mice which had undergone acute restraint stress differed from non-stressed controls in global hippocampal transcriptional responses. An up-regulation of transcripts contributing directly or indirectly to neurogenesis and neuronal protection including, Ttr, Rab6, Gh, Prl, Ndufb9 and Ndufa6, was observed. Systems level analyses revealed a significant enrichment for neurogenesis, neuron morphogenesis- and cognitive functions-related biological process terms and pathways. This work further supports the hypothesis that acute stress mediates a positive action on the hippocampus favouring the formation and the preservation of neurons, which will be discussed in the context of current data from the literature.